ANALISA PENERAPAN K3 PADA PEMELIHARAAN GARDU DISTRIBUSI LISTRIK DI PT. PLN (PERSERO) ULP CIKANDE MENGGUNAKAN METODE HIRADC - Wijaya, Hartadi; Rifki, Galang Ahmad; Gautama, Pugy (Prodi Teknik Industri, Fakultas Teknik, 2024)
This research was conducted at PT. PLN (Persero) ULP Cikande by analyzing employee occupational safety and health (K3) as a form of attention and protection in carrying out their duties. By using the HIRADC method, it is hoped that this research can provide the best solution for employee performance, especially in occupational safety and health (K3). From the results of collecting company work accident data, the risk matrix classification in 2022 obtained 2 variables with low risk, for the high risk level, 2 variables are obtained with a percentage of 40%, and for the medium risk level, 1 variable is obtained with a percentage of 20%. Proposed improvements in this study include changes in training, equipment maintenance, improved work procedures, and more careful risk assessment. With the cooperation and involvement of the entire team, we are confident that the implementation of this change will have a significant positive impact on the safety and welfare of all parties involved in substation inspections.